Pengaruh Product Quality, Price, dan Service Quality Terhadap Customer Satisfaction Pada PT. Trika Global Media (Trikamedia) Internet Access di Kabupaten Gianyar - I Nyoman Aris Parwita; Octavianus Sumardana Pratama; Anak Agung Istri Agung Ovy Dwijayanthi (Lembaga Penelitian Dan Publikasi Ilmiah (lppi) Yayasan Almahmudi Bin Dahlan, 2025)
Customer satisfaction is a key factor in maintaining customer loyalty and business sustainability, especially in service sectors such as internet providers. This study aims to evaluate how significantly product quality, pricing, and service quality influence customer satisfaction at PT. Trika Global Media (Trikamedia), a provider of internet access services in Gianyar Regency. A quantitative research method was employed, involving 98 respondents who are active Trikamedia customers. The data were analyzed using several techniques, including validity and reliability tests, classical assumption testing, multiple linear regression analysis, F-tests, t-tests, and the coefficient of determination. The findings reveal that product quality, price, and service quality both individually and collectively have a significant and positive impact on customer satisfaction.